SISTEM SOSIAL AL-QUR’AN - Ilyas Daud (Ibn Abbas : Jurnal Ilmu Alquran dan Tafsir, 2019)
This paper discusses about the social system of the Qur'an, using the reading through the theory of community development according to Karl Marx. The development of the social system of society according to Marx its began from the primitive communism system, the slavery, feudalism, capitalism, and socialism. The results of this reserch was showed that the social system of the Qur'an is an egalitarian form. This is as indicated in several verses among them QS. An-Nisa>: 1; Al-H{ujurat: 13; Al-Mu’minu>n: 32 and al-Anbiya>: 92. Nevertheless, despite teaching the human equality, the Qur'an also recognizes the existence of social differentiation. To overcome the monopoly of wealth, the Qur'an commands the distribution of wealth and prohibits the accumulation of property as in QS. Al-H{asr: 7 and al-Humazah: 1-4.